Activities Handout for Constellations - Magruder, Kerry; Purkaple, Brent (My University, 2016)
Suggested activities to be used in conjunction with Constellation Coloring Pages and Card Sets.
Keywords: Constellations; Physics, Astronomy and Astrophysics.; Music.; Literature, General.; Art History.; Art